The Power of Public Discourse - Dowsing, Kavita Abraham; Deane, James (2012)
The concept of open development presupposes a greatly increased supply of information available to citizens on the issues, products, and services that shape their lives. It means that governments should make information on budgets accessible and intelligible, local authorities should provide access to information about the provision of services that citizens can expect, and donors should be transparent about what they are spending, specifying for what and why, and doing so in forms that beneficiaries can use.